SUPERVISI KLINIS SEBAGAI STRATEGI PENINGKATAN KOMPETENSI PEDAGOGIK GURU DI ERA PENDIDIKAN ABAD KE-21 - Ika Verina; Yuli Dwi Bina Margarini; Rahman Afandi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to examine clinical supervision as a strategy for improving teachers' pedagogical competence in the era of 21st century education. Clinical supervision does not merely function as a performance evaluation instrument, but rather as a structured collaborative process between supervisors and teachers aimed at continuously improving the quality of learning. The method used is library research with a descriptive-analytical approach to various relevant primary and secondary sources, including academic works from the UIN Prof. K.H. Saifuddin Zuhri Purwokerto environment. The results of the study show that: (1) collaborative-based clinical supervision is able to significantly improve teachers' pedagogical competence; (2) the role of the school principal as a learning leader is crucial to the successful implementation of clinical supervision; (3) the integration of technology in clinical supervision opens new opportunities in teacher professional development; and (4) constructive feedback is the key to the success of the supervision process. These findings have important implications for education managers in designing teacher professional development programs that are adaptive to contemporary educational dynamics.